A Randomized, Open-Label, Single-Dose, Crossover Study of the Comparative Bioavailability of EPA and DHA in a Novel Liquid Crystalline Nanoparticle-Based Formulation of ω-3 Acid Ethyl Ester Versus Omacor® Soft Capsule among Healthy Adults - Kang, Kwi Man; Jeon, Sang Won; De, Anindita; Hong, Tae Sun; Park, Young Joon (International Journal of Molecular Sciences, 2023)
Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are well known for their capacity to lower triglyceride levels, but the clinical effectiveness is hindered by limited bioavailability and patient adherence. To address this challenge, we introduce a novel liquid crystalline nanoparticle-based formulation, the innovative medicine and drug delivery (IMD)-Omega soft capsule (cap), designed to optimize the pharmacokinetics (PK) and safety of EPA and DHA. This randomized, open-label, crossover study engages a cohort of 24 healthy adult subjects, utilizing key PK parameters like Cmax, AUC, Tmax, t½, and Ke to conduct a comprehensive evaluation. The trial compares the performance of the IMD-Omega soft cap with the well-established Omacor® soft cap. The IMD-Omega soft cap exhibited an impressive 110% increase in bioavailability for EPA and a remarkable 134% surge for DHA in comparison to the Omacor® soft cap over a span of 72 h. The key success can be attributed to the innovative liquid crystalline nanoparticle design, bolstering the dissolution and permeability of these essential fatty acids. Intriguingly, intra-participant variability for AUC0–72 h and Cmax were calculated at 45.04% and 34.26%, respectively. It is noteworthy that the parameters of Tmax for EPA (≈6.00 h) and DHA (≈5.00 h), t½ for both EPA and DHA ≈ 30–40 h, and Kel around 0.18–0.22 h−1 for EPA and ≈0.008–0.02 h−1 for DHA, displayed comparability between the IMD-Omega and Omacor® formulations. Encouragingly, the IMD-Omega soft cap showed excellent tolerability. The promise of optimized patient compliance and reduced dosages adds further weight to its potential significance.
Keywords: Adult; Biological Availability; Cross-Over Studies; Docosahexaenoic Acids; Eicosapentaenoic Acid; Esters; Fatty Acids, Omega-3; Humans; bioavailability; clinical trial; EPA and DHA; liquid crystalline nanoparticle; pharmacokinetics; safety